PERAN KEPALA DISTRIK DALAM PEMBINAAN DAN PENGAWASAN DANA KAMPUNG (DK) DI WILAYAH PEDALAMAN DISTRIK KOROWAY BULUANOP KABUPATEN ASMAT PROVINSI PAPUA SELATAN - Omet, Mikael (Jurnal Wahana Bina Pemerintahan, 2023)
This study was conducted to determine the role of the district Head in the guidance of village supervision in the rule since 2015 from removing the village funds until now. District in law No.23 of 2014 on Regional Government is part of the region of District/City. In this district law is a regional/city regional device that executes government affairs that become the authority of the region and also the administrative task. However, the existence of the district has been often regarded as a confusing government unit. The issuance of Law No.6 of 2014 on village makes the government should replicate the district role, whit the existence of the contemporarial government of whether the government is district only serve as a facilitator alone or still get authority to oversee village funds, from the results of this study the Koowerow District Government of Buluanop is work of activities (Kun-Ker) and evaluation which is a direct duration of the district, work visits and evaluation which is a regular activity of the district government in overseeing the implementation of village funds, conducted by coming to monitor as well as check the activities implemented by the village apparatus, administrative checks, liquid funds, the allocation of village funds, checking the construction of the village from measuring the land to the checking of the building. However, the supervision is only to monitor the village funds to the extent of the ones and do whether the completeness of the data is available, since there is no continuous surveillance of the district, subsequent supervision is directly done by APIP regency/city. The district government also performs indirect control checking the document-document of the village which is always reported to the district, both RPJMDes, RKPDes, BKK, and others, so indirectly the district also oversees the village finance through the reported document.